Use a suitable identity to get each of the following products.
(7a - 9b) (7a - 9b)
Using the identity, (a - b)2 = a2 - 2ab + b2 we have
(7a - 9b) (7a - 9b) = ( 7a -9b)2
= (7a)2 - 2(7a)(9b) + (9b)2
= 49a2 - 126ab + 81b2
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(i) (x + 3) (x + 7)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(4x + 5) (4x + 1)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(4x - 5) (4x - 1)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(4x + 5) (4x - 1)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(2x +5y) (2x + 3y)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(2a2 + 9) (2a2 + 5)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(xyz - 4) (xyz - 2)